Penerapan Nilai-Nilai Sistem bagi Hasil Mukhabarah pada Peningkatan Profitabilitas dalam Perspektif Keuangan Syariah (Studi Kasus Petani Rumput Laut Di Kel. Pallette Kec. Tanete Riattang Timur Kab. Bone) - Herwinda; Abd Rasyid R; Rahma Hidayati (Journal of Mandalika Literature, 2025)
This study aims to determine how the application of the values ​​of the profit sharing system of mukhabarah on increasing profitability in the perspective of sharia finance of seaweed farmers in Pallette Village, East Tanete Riattang District, Bone Regency. Based on the problems above, the approach used in this study is a qualitative approach using a phenomenological strategy. By describing in the form of words that are in accordance with the experiences experienced by the informants. Supported by theory as the basis for research development, also supported by observation, interviews, and documentation in collecting the necessary data. From the data collected, it was analyzed descriptively. The data analysis was used to determine the application of the values ​​of the profit sharing system of mukhabarah on increasing profitability in the perspective of sharia finance of seaweed farmers in Pallette Village, East Tanete Riattang District, Bone Regency. application of the values ​​of the profit sharing system of mukhabarah on seaweed farmers applied in Pallette Village, East Tanete Riattang District, Bone Regency. Bone has fulfilled the requirements and pillars of the mukhabarah contract. Although the community is still unfamiliar with the term mukhabarah and the majority admits to not knowing whether the practices carried out are appropriate or not, in reality the community has implemented it even though it is not truly kaffa